Organisms Diversity & Evolution - Wanninger, Andreas; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Organisms Diversity & Evolution (published by the Gesellschaft fuer Biologische Systematik, GfBS) is devoted to furthering our understanding of all aspects of organismal diversity and evolution. Papers addressing evolutionary aspects of the systematics, phylogenetics, morphology and development, taxonomy and biogeography of any group of eukaryotes, recent or fossil, are welcome. Priority is given to papers with a strong evolutionary and/or phylogenetic focus. Manuscripts presenting important methods or tools or addressing key theoretical, methodological, and philosophical principles related to the study of organismal diversity are also welcome. Species descriptions are welcome as parts of a manuscript of broader interest that strive to integrate such taxonomic information with the other areas of interest mentioned above. Published articles are of one of the following four types: Original article. Papers describing original, high-quality research in any of the areas mentioned above. Methods papers. Short papers (<5 journal pages) describing new laboratory methods, bioinformatic tools, or databases that will facilitate research into organismal diversity. Forum paper. Papers discussing issues relevant to the main areas of interest of the journal and their related science politics. Review. Reviews of topics relevant to the journal. If you plan to submit a review, please contact the Editor-in-Chief by email at andreas.wanninger@univie.ac.at. Emerging Discussion. If you disagree with certain statements made in a paper published in Organisms Diversity & Evolution, you may want to send an (3z(BEmerging Discussion.(3y (BPlease always contact the Editor-in-Chief before submission by email at andreas.wanninger@univie.ac.at.s
Keywords: Developmental biology; Biodiversity; Evolutionary biology; Plant systematics; Plant taxonomy; Animal systematics; Animal taxonomy; Biodiversity; Evolutionary Biology; Developmental Biology; Animal Systematics/Taxonomy/Biogeography.; Plant Systematics/Taxonomy/Biogeography.